2014
DOI: 10.3748/wjg.v20.i10.2634
|View full text |Cite
|
Sign up to set email alerts
|

Serrated pathway in colorectal carcinogenesis

Abstract: Serrated adenocarcinoma is a recently described subset of colorectal cancer (CRC), which account for about 10% of all CRCs and follows an alternative pathway in which serrated polyps replace the traditional adenoma as the precursor lesion to CRC. Serrated polyps form a heterogeneous group of colorectal lesions that includes hyperplastic polyps (HPs), sessile serrated adenoma (SSA), traditional serrated adenoma (TSA) and mixed polyps. HPs are the most common serrated polyp followed by SSA and TSA. This distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 51 publications
0
82
0
6
Order By: Relevance
“…Thus we now understand that the serrated pathway is a route through which 10-30% of CRC develop 14,15 . This was supported by a recent systematic review and meta-analysis, by Gao et al, revealing a strong positive relationship between proximal SP and synchronous advanced neoplasia 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus we now understand that the serrated pathway is a route through which 10-30% of CRC develop 14,15 . This was supported by a recent systematic review and meta-analysis, by Gao et al, revealing a strong positive relationship between proximal SP and synchronous advanced neoplasia 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, EGFR, the target of these drugs, which is overexpressed in approximately 50.0–80.0% of CRC, failed to predict a therapeutic response when used clinically. Research showed that the Kirsten rat sarcoma viral oncogene homolog ( KRAS ) gene, an important member of the EGFR signalling cascade, can acquire activating mutations in exon 2 codons 12 and 13 in approximately 35.0–45.0% of the CRC cases, rendering EGFR inhibitors ineffective [4, 5]. In 2009, the US Food and Drug Administration (FDA) approved EGFR-targeted monoclonal antibody therapy with cetuximab and panitumumab in patients with metastatic colorectal cancer (mCRC) along with analysis of KRAS mutation status, which is a predictive biological marker of resistance [68].…”
Section: Introductionmentioning
confidence: 99%
“…Adenoma is the principal precursor lesion of CRC (5,6) but, recently, serrated polyp was recognized as an alternative precursor lesion of CRC and follows an alternative pathway in which serrated polyp replaces the traditional adenoma as the precursor lesion to serrated CRC, accounting for ~10% of all CRCs (7,8). Serrated polyps form a heterogeneous group of colorectal lesions that include hyperplastic polyps (HPs), sessile serrated adenoma (SSA), traditional serrated adenoma (TSA) and a combination of two or more characteristics, formerly classified as mixed polyps (MP) (9). HPs are the most common serrated polyp and they have been increasingly suggested to be precursor lesions, since they may develop into other serrated polyps as SSA, TSA or MP to CRC (10).…”
Section: Introductionmentioning
confidence: 99%